Sukseskan Gerakan Wanita Matilda (Mandiri, Terampil, Berdaya) di RT 49 Kelurahan Sepinggan - Rahayu Sri Waskitoningtyas; Nur Ismiyati (Abdimas Universal, 2020)
This study aims to find out how PKK RT 49 RT Sepinggan Balikpapan urban residents conduct urban farming. This service was carried out in RT 49, Sepinggan Village. The subjects of this study were the residents of RT 49, Sepinggan Village. Sampling is based on random sampling. Data collection through observation and documentation. Urban Farming is beneficial for RT 49 mothers, through urban faming mothers can grow vegetables in their own yards. If you don't have a yard, you can do it using used pots, buckets and used tins. Vegetables grown in the form of chili, tomatoes, onions, lime and pumpkin.